Profile of secukinumab in the treatment of psoriasis: current perspectives - Roman M; Madkan VK; Chiu MW (Dove Medical Press, 2015)
Michael Roman, Vandana K Madkan, Melvin W Chiu Division of Dermatology, David Geffen School of Medicine at UCLA, Los Angeles, CA, USA Abstract: Secukinumab (Cosentyx™) is a human monoclonal IgG1k antibody that has been developed to target and block the actions of IL-17A. It is known that this cytokine is elevated in lesions of psoriasis. Interleukins in the Th17 pathway play a pivotal role in the pathogenesis of psoriasis and have thus become targets for recent biologic drug development. As a monoclonal antibody immune modulator, secukinumab exhibits the expected pharmacokinetic properties of slow subcutaneous absorption, low clearance, and long half-life, although formal studies examining the impact of impaired hepatic or renal function on the overall pharmacokinetic profile have not been conducted. Both Phase II and III clinical trials have demonstrated the effectiveness of secukinumab in the treatment of moderate-to-severe plaque psoriasis, psoriatic arthritis, rheumatoid arthritis, ankylosing spondylitis, and noninfectious uveitis. In June 2015, secukinumab was approved by the US Food and Drug Administration for the treatment of adults with moderate-to-severe plaque psoriasis, with a wealth of clinical trials showcasing its efficacy in improving psoriasis area and severity index scores, and it is superior to other comparable biologics on the market, including the TNF inhibitor etanercept. As such, this review focuses on the marquee clinical trials involving secukinumab treatment of plaque psoriasis, while also exploring this drug’s efficacy in treating patients with psoriatic arthritis, a disease that has a well-documented comorbidity in patients diagnosed with moderate-to-severe plaque psoriasis. Finally, the safety and tolerability of this drug in a variety of clinical trials to date have also been reviewed, and will undoubtedly have a large impact on this drug’s postmarketing surveillance and future studies regarding its long-term safety. Keywords: biologics, IL-17, psoriatic arthritis